2001
DOI: 10.1039/b108072p
|View full text |Cite
|
Sign up to set email alerts
|

Effects of electron withdrawing and donating groups on the efficiency of tris(2,2′-bipyridyl)ruthenium(ii)/tri-n-propylamine electrochemiluminescence

Abstract: The effects of electron withdrawing and electron donating groups on the electrochemiluminescent (ECL) properties of tris(2,2'-bipyridyl)ruthenium(II) (Ru(bpy)3(2+) where bpy = 2,2'-pyridine) are reported. The electrochemistry, photophysics and ECL of (bpy)2Ru(DC-bpy)2+, and (bpy)2Ru(DM-bpy)2+ (DC = 4,4'-dicarboxy-2,2'-bipyridine; DM = 4,4'-dimethyl-2,2'-bipyridine) have been studied relative to Ru(bpy)3(2+) in 50:50 (v/v) acetonitrile(CH3CN):H2O (0.1 M KH2PO4), and aqueous solutions. Furthermore, the effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 15 publications
3
33
0
Order By: Relevance
“…The results indicated that the different Ru(bpy) 3 2þ derivatives could not lead to dramatic increase or decrease in ECL efficiency but the adsorption of TPA or other factors contribute to the surfactants effect [15]. In the present work, the difference in solubility between TPA and TMBA results in their different responses to the added surfactants.…”
Section: þmentioning
confidence: 92%
See 1 more Smart Citation
“…The results indicated that the different Ru(bpy) 3 2þ derivatives could not lead to dramatic increase or decrease in ECL efficiency but the adsorption of TPA or other factors contribute to the surfactants effect [15]. In the present work, the difference in solubility between TPA and TMBA results in their different responses to the added surfactants.…”
Section: þmentioning
confidence: 92%
“…Bruce et al [15] gave a novel protocol to validate the effects of surfactant on ECL emission. Various carboxyland methyl-groups were attached to the bipyridyl group of Ru(bpy) 3 2þ , and therefore, changed the hydrophobicity of Ru(bpy) 3…”
Section: Surfactant Effects On the Ecl Emissionsmentioning
confidence: 99%
“…Ru(bpy) 3 2+ based ECL system can emit light at room temperature in both aqueous and non-aqueous solutions with relatively higher ECL efficiency. The ECL reaction of Ru(bpy) 3 2+ with TPA has been well investigated by many workers [3,12,13]. Scheme 1 describes the general ECL mechanism where the oxidation of TPA generates a strongly reducing specie of TPA・ [3].…”
Section: +mentioning
confidence: 99%
“…The principle and reaction mechanism of Ru(bpy) 2þ 3 with TPA have been studied in many works [3,19,20] …”
Section: Principle Of the Sensormentioning
confidence: 99%